Isolation and Screening of Polyhydroxyalkanoates (PHA) Producing Bacteria Utilizing Agricultural Waste - Afghan, Inzer Gul; Shrivastav, Anupama (International Journal of Applied Sciences and Biotechnology, 2020)
Polyhydroxyalkanoates (PHAs) are biosynthetic, environmentally friendly and biodegradable polyester stored as a granules inside the cytoplasm of microorganisms, granules are compounds of PHAs used as carbon and energy source, Synthetic polymer take many years to demolish completely, microorganisms can degrade PHAs within a year into carbon dioxide, water and energy, The main contributor for PHAs production cost is carbon sources cost, Accordingly it is favorable to produce PHA from any agriculture waste like rice bran. Aim of this dissertation is to utilize rice bran which was obtained from Limda field near Parul University, screening and isolation of polyhydroxyalkanoates PHAs producing bacteria, Synthesis of most effective PHB, different wild type microorganisms were studied by flask shaking method to determine their ability to produce PHA utilizing rice bran as carbon source, Total 16 isolates showed the fluorescence in the presence of Nile blue in solid medium under UV light, two bacterial isolates SF-3 and SF-2 isolated from jaggery waste, respectively, PHA Accumulation for (2%RB-1%) and (2%RB-5%) was 68% and 47% PHA/(CDW) respectively, the PHB obtain from (2%RB-1%) and (2%RB-5%) was analyzed by FTIR and NMR as poly hydroxyl butyrate (PHB).Int. J. Appl. Sci. Biotechnol. Vol 8(3): 336-342